Actualité du roman archéologique - Philippe Dufour (Flaubert: Revue Critique et Génétique)
Some scholars like Anne Green have shown that Flaubert in his historical novel, Salammbô, frequently alludes to contemporary history in spite of the obvious difference between the Carthaginian civilization and the modern world. In this essay I will try to grasp the shift in referenciality through a small description (a meeting between the wealthy), inspired by Aristotle’s Politics: Hugolian images of decadence from Les Châtiments appear superimposed on it, so that the archeological novel turns into an allegorical satire on the Second Empire.